Teachers’ and Students’ Experiences in Using Kinesthetic Games to Practice Prepositions of Place - Susanti Olivia Malau; Fitra Kurniawan Halawa; Alvita Aprilia Br Sembiring; Juwita Rahmina Siva Sari; Desrina Damaiyanti Br Ginting; Natalia Widya Pasca Tarigan (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study examines the experiences of English lecturers and nursing students utilising kinaesthetic games to learn prepositions of place in an English for Nursing course in Medan, Indonesia. Employing a qualitative descriptive design, data were gathered via classroom observations, semi-structured interviews, and documentation. The findings indicate three primary themes: lecturers' experiences in employing kinaesthetic games, students' learning experiences, and the perceived advantages and challenges of the methodology. Both teachers and students said that kinaesthetic games made the classroom more lively, interesting, and interactive. Activities that involved movement helped students understand spatial meanings better, made them more confident, and made them less anxious about grammar. The games also helped kids work together and remember things better. But there were some problems, such as not enough room in the classroom, not enough time to get ready, and more noise. In general, the study finds that kinaesthetic games are a good way to teach prepositions of place in the Indonesian EFL nursing context. They have cognitive, emotional, and social benefits that help students learn grammar in a more meaningful way.